Report on the Peace Corps conference : women in development and the role of the peace corps volunteer - Hekey, Kay; Corbett, Susan (Monrovia: Peace Corps - Liberia, 1979)
"Een confrentie bijeengeroepen door : Peace Corps - Liberia, in samenwerking met Peace Corps - Sierra Lone en Peace Korps - Ivory Coast"